Comparison of naturally acquired parasite burdens among Florida Native, Rambouillet and crossbreed ewes - Amarante, AFT; Craig, T. M.; Ramsey, W. S.; El-Sayed, N. M.; Desouki, A. Y.; Bazer, F. W. (Elsevier B.V., 1999)
The response to natural infection by gastrointestinal nematodes was evaluated in three groups of lambing mature ewes: 16 Florida Native; 21 Rambouillet; and 18 1/2 Florida Native x 1/2 Rambouillet (F1 generation). Fecal egg counts (FEC),packed cell volume (PCV) and plasma protein levels were determined periodically through a one-year period. The highest FEC was recorded in Rambouillet ewes, with most of the means higher than 1000 eggs per gram (EPG). Florida Native and Fl ewes showed similar trends in FEC, with most of the means below 500 EPG. The highest mean PCV values were recorded in Florida Native ewes, followed in decreasing order by Fl and Rambouillet ewes. Fl ewes showed the lowest plasma protein levels and Florida Natives the highest. Fecal cultures revealed the highest percentages of Haemonchus larvae in Rambouillet ewes (>64%) and the lowest percentages in Florida Native ewes. Florida Native and Fl ewes were more resistant to gastrointestinal nematode infections than were Rambouillet ewes. High negative correlation coefficients between FEC x PCV and FEC x plasma protein levels coincided with peaks in mean FEC of Rambouillet (May and July), Florida Native and Fl ewes (October). This study showed that crossbreeding Rambouillet and Florida Native sheep resulted in the production of Fl ewes resistant against gastrointestinal nematode infections. (C) 1999 Elsevier B.V. B.V. All rights reserved.
Keywords: sheep-nematoda; rambouillet; Florida native; drug resistance; F1 generation